Analyzing the Linkages between Diaspora Remittances, Institutions, and Self-Employed Business Activities: Insights from an Emerging Economy - Olubodun, Idowu Emmanuel; Dada, James Temitope; Ayeni, Adebanji A. W.; Osotimehin, Kehinde Oso (Organizations and Markets in Emerging Economies, 2025)
Diaspora remittance either smooths consumption, boosts welfare among recipients, or enhances the balance of payment in economies such as developing nations. Nonetheless, institutions that support its usefulness for financing business are always a concern, as they may not encourage interest in self-employment. The study investigates the linkages between diaspora remittances, institutions, and self-employed business activities. The integration is essential for promoting entrepreneurship while solving the unemployment problem. Annual time series data sets covering the period from 1991 to 2020. were used in Nigeria. The autoregressive distributed lag (ARDL) is used as the baseline. Three long-run estimate techniques are used for sensitivity analysis. The short-run coefficient of diaspora remittance on self-employment is positive and significant. In the long run, the effect of diaspora remittance on self-employment is significantly negative. It shows that diaspora remittances are used for immediate consumption, rather than translating into long-term employment generation in Nigeria. However, the impact of institutions on self-employment, in the short and long run, is significantly negative revealing poor institutions that are inadequate for employment creation. Due to poor institutional quality, diaspora remittances do not translate to long-run self-employment creation. Policymakers must strengthen the institutional environment to incentivize diasporans to remit.